Tropospheric Rossby Wave Breaking and the SAM - Wang, Yi-Hui; Magnusdottir, Gudrun (Journal of Climate, 2011)
An objective analysis of tropospheric anticyclonic- and cyclonic-breaking Rossby waves is performed for the Southern Hemisphere in austral summer (December–February) of 1979–2009. The climatology of both anticyclonic and cyclonic Rossby wave breaking (RWB) frequency is presented. The frequency of anticyclonic RWB is highest in an extended region of the Eastern Hemisphere on the anticyclonic side of the jet, while that of cyclonic RWB is highest on the cyclonic side of the jet. A composite analysis of anticyclonic and cyclonic RWB shows how they contribute to a positive and negative southern annual mode (SAM) index, respectively. The time series of austral summer anticyclonic RWB occurrence has a trend that closely matches the trend in the SAM index. Regions of RWB that are significantly correlated with the SAM index are objectively determined. Even though several such regions are identified, only two regions (anticyclonic and cyclonic) covering 17% of the area of the hemisphere are required in a linear regression model of the SAM index. The anticyclonic RWB region is zonally extended at 45°S and explains 78% of the variability of the summer-mean SAM index. The cyclonic region is located at high latitudes somewhat decoupled from the jet, in the longitudinal sector of the Indian Ocean. On synoptic time scales, transitions of the SAM index respond to RWB without time lag. ENSO cycles present an interesting zonal asymmetry to the distribution of Southern Hemispheric RWB in the central Pacific. Anticyclonic RWB is increased in the tropical/subtropical central Pacific during La Niña compared to El Niño. This increase is related to the strong local decrease in zonal wind. At the same time, anticyclonic RWB outside the central Pacific is increased in frequency poleward and decreased in frequency equatorward of 42°S, corresponding to a positive SAM index.